At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

For any value of x, the sum
3
∑ k(2x-1)
k=0
is equivalent to


Sagot :

The equivalent value of the sum for any value of "x" is 12x - 6

How to find the sum of functions?

Given the sum of the expression as:

3

∑ k(2x-1)

k=0

We need to take the sum of the function at the point where k = 0 to 3

3

∑ k(2x-1) = 0(2x-1) + 1(2x - 1) + 2(2x-1) + 3(2x - 1)

k=0

3

∑ k(2x-1) = 2x-1+4x-2+6x-3

k=0

3

∑ k(2x-1) = 12x - 6

k=0

Hence the equivalent value of the sum for any value of "x" is 12x - 6

Learn more on sum functions here: https://brainly.com/question/24295771